In situ experimental study of CO2 gasification of petcoke particles on molten slag surface at high temperature. (1st February 2021) - Liu, Ming; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: The catalytic effect of slag on petcoke gasification on molten slag surface was demonstrated. The catalytic effects realized only when the petcoke particle and molten slag exist direct contact. The surface reaction area of petcoke particles on molten slag surface was decreased. Floating motion of char particle increased contacting area between slag and char. Abstract: The gasification reaction of petcoke on wall slag layer was an important issue that should be studied during the co-gasification process of coal and petcoke. In present work, the gasification characteristics of petcoke particles on molten slag surface was investigated using a high temperature stage microscope. The catalytic effect of slag on petcoke gasification on slag surface was demonstrated. The experimental results demonstrated that the catalytic effect of slag only worked when the particle was on the surface of slag. The catalyst vapor had no influence on the reactivity of petcoke. What's more, the SEM analysis result showed that the reaction surface area of petcoke was decreased as a result of the deposition process. The effect of molten slag on particle temperature could be neglected as a result of the weak endothermic effect. Therefore, the change of petcoke reactivity rely on the synergy between catalytic effect of slag and the decreased reaction surface area. Besides, the increased residence time of petcoke also could increase the carbon conversion compared with that in gasifier chamber.